2012
DOI: 10.1097/fbp.0b013e3283512c1e
|View full text |Cite
|
Sign up to set email alerts
|

A single injection of a novel kappa opioid receptor agonist salvinorin A attenuates the expression of cocaine-induced behavioral sensitization in rats

Abstract: Kappa opioid receptor (KOPr) activation antagonizes many cocaine-related behaviors but adverse side effects such as sedation, dysphoria and depression limit their therapeutic use. Recently, salvinorin A (Sal A), a naturally occurring KOPr agonist, has been shown to attenuate cocaine-induced drug-seeking in a model of relapse in rats. The present study evaluated the effects of acute Sal A exposure on cocaine-induced hyperactivity and cocaine sensitization in rats. Acute treatment with the dose of Sal A that dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(86 citation statements)
references
References 78 publications
6
75
0
Order By: Relevance
“…It also attenuates the effects of cocaine hyperactivity when administered acutely, but potentiates the same effects when chronically administered. On the other hand, low doses of Sal A (< 0.25 mg/kg) (ip) consistently display less aversive effects (Morani et al, 2009; Morani et al, 2012) and is within the range with known anti-cocaine effects. Given this, Sal A possesses desirable anti-addiction effects with fewer side effects compared to traditional KOPr agonists.…”
Section: Animal Studies With Salvinorin Amentioning
confidence: 89%
See 3 more Smart Citations
“…It also attenuates the effects of cocaine hyperactivity when administered acutely, but potentiates the same effects when chronically administered. On the other hand, low doses of Sal A (< 0.25 mg/kg) (ip) consistently display less aversive effects (Morani et al, 2009; Morani et al, 2012) and is within the range with known anti-cocaine effects. Given this, Sal A possesses desirable anti-addiction effects with fewer side effects compared to traditional KOPr agonists.…”
Section: Animal Studies With Salvinorin Amentioning
confidence: 89%
“…Recently Sal A (0.3mg/kg) was shown to attenuate cocaine-prime-induced reinstatement, similar to U69,593 (0.3 mg/kg), U50,488 (30 mg/kg) and spiradoline (1 mg/kg) (Morani et al, 2009). Sal A also attenuated the expression of cocaine-induced behavioural sensitization in rats (Morani et al, 2012) comparable to U69,593 (Heidbreder, Babovicvuksanovic, Shoaib, & Shippenberg, 1995). The decrease in cocaine self-administration with traditional KOPr agonist U69,593 was accompanied by a decrease in food intake in rhesus monkeys (Mello & Negus, 1998; Negus, et al, 1997) and decreases in self-administration were only apparent when rats were trained with a cue (Schenk, Partridge, & Shippenberg, 1999).…”
Section: Animal Studies With Salvinorin Amentioning
confidence: 94%
See 2 more Smart Citations
“…The rewarding effects of salvinorin A were also reported by other authors, implicating the involvement or "cross-talk" of the endocannabinoid system in the mechanism of this action (Capasso et al 2008;Walentiny et al 2010). It has been also shown that salvinorin A may decrease responses to cocaine and in this way attenuate cocaine-induced drug-seeking behavior (Chartoff et al 2008;Morani et al 2009Morani et al , 2012.…”
Section: Biological Activitymentioning
confidence: 97%